If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + 12v = -7v + -20 Reorder the terms: -1 + 12v = -20 + -7v Solving -1 + 12v = -20 + -7v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '7v' to each side of the equation. -1 + 12v + 7v = -20 + -7v + 7v Combine like terms: 12v + 7v = 19v -1 + 19v = -20 + -7v + 7v Combine like terms: -7v + 7v = 0 -1 + 19v = -20 + 0 -1 + 19v = -20 Add '1' to each side of the equation. -1 + 1 + 19v = -20 + 1 Combine like terms: -1 + 1 = 0 0 + 19v = -20 + 1 19v = -20 + 1 Combine like terms: -20 + 1 = -19 19v = -19 Divide each side by '19'. v = -1 Simplifying v = -1
| -6+8q=-4+5q+5q | | 5x^2+4x+11= | | 2(x-1)-(8x-1)=0 | | 14s-9=18s+15 | | -9(-7d+3)-4d=-4(-16d-2) | | 8-19d=-10-2d-16 | | 210=5x+125 | | 1x+3*3=14 | | -6+8p=8+10p | | 16+b=84 | | 5x-2(x+4)=7x+2 | | 18+f=-5f | | 7h+7=8h | | -4(-6-15u)=-3(12-16u) | | 4x^4=2-7x^2 | | f-8=2f | | 15x^2-11x+11= | | 8+t=-9t-2 | | 2+6b=-4+7b | | -3(-z-6)=6z | | 10+2b=-10+4b | | -6+x^4=-5 | | 9j=10j-10 | | -7t=-6t-13 | | A-17=19 | | 3(-18q+15)=-3(19q-16) | | 1+2x=-3x+41 | | 4(2-x)=-2(x+7)-2x | | 5g=8g+6 | | 10+7-j=-10j-10 | | -9+8z=9+6z | | -6(-5f+18)-17f=19f |